Фестивальна регіональна практика в проблемному ціннісному аспекті сучасної культурної ситуації - Корольчук, Ольга Леонідівна; Виткалов, Сергій Володимирович; Korolchuk, Olha L.; Vytkalov, Serhii V. (Рівненський державний гуманітарний університет, 2015)
Аналізується роль і значення фестивальних заходів, проведених на регіональному рівні, у формуванні ціннісних орієнтацій сучасного населення; виявляється їх значення у системі культурного обслуговування. The role of festival measures is analyses in the system of cultural maintenance of modern population; the specific of regional level appears, problem row in organization of the system of cultural service. Attention is accented on importance of the begun reform of local self-government, which must stimulate the leaders of local level to the search of corresponding specialists in organizations of this service, or adjusting of the own system of training of professional personals of sphere of culture. The festival row of measures which will get organized in the different regions of Ukraine and their value appears in modern cultural practice is examined. Most actual проблематику which interests a local population in the field of leisure is shown. It is marked importance of such measures in the general system of forming of artistic culture of children. It is marked on the important line of artistic festivals - contentedness which stimulates the exposure of cultural initiative at any categories of population.
Festival regional practice is in the problem valued aspect of modern cultural situation
Keywords: фестиваль; регіон; культурно-мистецька практика; ціннісні орієнтації; festival; region; cultural and art practice; valued orientations